DEVELOPMENT OF AN INCOMING MAIL ADMINISTRATION MODEL IN THE PROTOCOL AND LEADERSHIP COMMUNICATION DIVISION OF BANDAR LAMPUNG CITY - Agastia Pramesti Regita Cahyani P; Budhi Waskito (International Journal of Multidisciplinary Reseach, 2026)
The research method used is qualitative descriptive research. This method is used to describe the effectiveness of Land and Building Tax (PBB) Collection Through an Online Application in Tejo Agung Village, Metro Timur District, Metro City. All data were obtained directly from informants in the field using interviews and document studies. The research results show that the effectiveness of Land and Building Tax (PBB) collection through online applications in Tejo Agung Village is influenced by several inhibiting aspects that can be classified based on the following dimensions: (1) Time unit dimension, where the collection process is hampered by limited technology and network infrastructure, resulting in slow access and data processing, resulting in suboptimal service times. (2) Results unit dimension, where low taxpayer participation in utilizing online applications and a lack of outreach results in less than optimal tax revenue realization and difficulties in achieving the expected targets. (3) Meanwhile, in the work quality dimension, limited competency and motivation of officials in managing online applications, along with an increased workload, impact inadequate service quality, thereby reducing the overall effectiveness of tax collection.